2005
DOI: 10.2174/138620705774962391
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Biomarker Candidates by Differential Peptidomics Analysis of Cerebrospinal Fluid in Alzheimers Disease

Abstract: The objective of this work was the application of peptidomics technologies for the detection and identification of reliable and robust biomarkers for Alzheimer's disease (AD) contributing to facilitate and further improve the diagnosis of AD. Using a new method for the comprehensive and comparative profiling of peptides, the differential peptide display (DPD), 312 cerebrospinal fluid (CSF) samples from AD patients, cognitively unimpaired subjects and from patients suffering from other primary dementia disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…The reported upregulation of VGF in the CSF of subjects with schizophrenia (Huang et al, 2006) may be explained by the differential kinetics of mRNA versus peptide metabolites in the CSF or by differences in the disease population. Consistent with our findings, a VGF peptide was reported to be decreased in CSF in neurodegenerative diseases (Ranganathan et al, 2005;Rüetschi et al, 2005;Selle et al, 2005;Zhao et al, 2008). VGF levels are also downregulated in leukocytes of depressed patients but are restored in response to antidepressant treatment (Cattaneo et al, 2010).…”
Section: Vgf Mrna Is Reduced In Human Bipolar Postmortem Brainssupporting
confidence: 90%
“…The reported upregulation of VGF in the CSF of subjects with schizophrenia (Huang et al, 2006) may be explained by the differential kinetics of mRNA versus peptide metabolites in the CSF or by differences in the disease population. Consistent with our findings, a VGF peptide was reported to be decreased in CSF in neurodegenerative diseases (Ranganathan et al, 2005;Rüetschi et al, 2005;Selle et al, 2005;Zhao et al, 2008). VGF levels are also downregulated in leukocytes of depressed patients but are restored in response to antidepressant treatment (Cattaneo et al, 2010).…”
Section: Vgf Mrna Is Reduced In Human Bipolar Postmortem Brainssupporting
confidence: 90%
“…The action of prohormone convertases PC1/3 and PC2 on the VGF precursor has been studied, and showed that PC1/3 is responsible for cleavage at the N-terminus of TLQP and other peptides (Trani et al 2002), in keeping with the accumulation of the C-terminal VGF-derived peptide V in mice lacking PC1/3 (Pan et al 2005). Conversely, the enzyme/s affecting C-terminal cleavage of TLQP-21, as well as others involved in the production of multiple VGF peptides revealed in the human cerebro-spinal fluid (Selle et al 2005) remain to be clarified. A parallel is often drawn between VGF and the chromograninsecretogranin family of proteins, because of their selective localisation in secretory granules, as well as their role as precursors of multiple bioactive peptides (Helle 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to establish if the changes of VGF can be disease specific or, alternatively, if the combined analysis of different neuropeptides would prove useful for diagnostic purposes as well as to establish treatment responsiveness. In this regard, it has to be noticed that VGF levels have been found altered also in patients with amyotrophic lateral sclerosis (ALS) and Alzheimer's disease (Selle et al, 2005;Pasinetti et al, 2006;Zhao et al, 2008). Under these conditions it has been proposed that changes in VGF expression may promote neurodegeneration, through NMDA-and AMPA-mediated exitotoxic injury.…”
Section: Vgf Modulation In Major Depressionmentioning
confidence: 99%